2018
DOI: 10.1186/s11671-018-2820-y
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-containing supramolecular nanoparticles based on bipyridine-modified cyclodextrin and adamantyl PEI with DNA condensation properties

Abstract: Exploring safe and highly efficient gene carriers made from biocompatible constituents has great prospects for clinical gene therapy. Here, a supramolecular gene delivery system was readily constructed by assembling adamantyl-modified polyethylenimine (PEI-Ada) units with a versatile ruthenium bipyridine-modified cyclodextrin (Ru-CD) through host-guest interactions. The photophysical and morphological features of the PEI-Ada@Ru-CD nanoparticles were systematically characterized by techniques including UV-vis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Hydroxyl groups can also be used for bioconjugation or polymerization 168 . CD and its derivatives are naturally available, water‐soluble, biocompatible, and exert a negligible level of toxicity 173 . Although “pure” CD vectors exist for gene therapy, CDs are often used as one of several components of gene delivery systems.…”
Section: Biomaterial‐based Nucleic Acid Delivery Systemsmentioning
confidence: 99%
“…Hydroxyl groups can also be used for bioconjugation or polymerization 168 . CD and its derivatives are naturally available, water‐soluble, biocompatible, and exert a negligible level of toxicity 173 . Although “pure” CD vectors exist for gene therapy, CDs are often used as one of several components of gene delivery systems.…”
Section: Biomaterial‐based Nucleic Acid Delivery Systemsmentioning
confidence: 99%
“…However, cationic polymers are currently limited in their use, in part due to low uptake and efficiency, toxicity, and immunogenicity. To help mitigate some of these concerns, many groups have worked to introduce CDs to traditional cationic polymer systems, and have shown that these CD-integrating formulations successfully deliver pDNA [44][45][46][47][48][49] and various RNAs [16,[50][51][52] for gene editing and gene modulation. In general, these delivery systems show greater efficacy and lower toxicity than similar formulations which do not incorporate CD.…”
Section: Cationic Polymersmentioning
confidence: 99%
“…By incorporating CD into PEI delivery systems, toxicity concerns can be alleviated by shortening the molecular weight of PEI used while retaining its gene transfection properties. In fact, formulations which include CD show improved DNA condensation over PEI alone [48]. An example of CD incorporation is the synthesis of PEI-β-CD, through creation of amine-reactive CD and conjugation to the amines found in branched PEI [68].…”
Section: Cationic Polymersmentioning
confidence: 99%
See 2 more Smart Citations